Quantifying Persecution: Developing an International Law-based Measurement of Freedom of Religion or Belief - Gatti, Mauro (The review of faith & international affairs, 2019)
In this essay the authors-an international and interdisciplinary research team of scholars and practitioners-present the main challenges they faced, the solutions they developed, and their reflections and recommendations based on their research for the annual report of the European Parliament Intergroup on Freedom of Religion or Belief & Religious Tolerance. The research team elucidated international law standards on FoRB and then assessed whether the laws and practices of third countries are consistent with their international legal obligations. This grounding in international law is a distinctive contribution of the research.